“Natural Laboratory Complex” for novel primate neuroscience - Iriki, Atsushi; Tramacere, Antonella (Frontiers in Integrative Neuroscience, 2022)
We propose novel strategies for primate experimentation that are ethically valuable and pragmatically useful for integrative neuroscience research. Specifically, we propose Natural laboratory Complex or Natural-Labs, which are a combination of indoor-outdoor structures for studying free moving and socially housed primates in natural or naturalistic environment. We contend that Natural-Labs are pivotal to improve primate welfare, and at the same time to increase validity of longitudinal and socio-ecological studies of primate brain and behavior. Currently emerging advanced technologies and social systems (incl. recent COVID-19 induced “remote” infrastructures) can speed-up integrative neuroscience approaches in freely behaving animals. Integrative approaches in natural(istic) experimental settings are not in competition with conventional approaches of laboratory investigations, and could establish several benefits at the ethical, experimental, and economic levels.